Exposure‐response analysis for nivolumab plus ipilimumab combination therapy in patients with advanced hepatocellular carcinoma (CheckMate 040) - Bruno Sangro; Thomas Yau; Anthony B. El‐Khoueiry; Masatoshi Kudo; Yun Shen; Marina Tschaika; Amit Roy; Yan Feng; Ling Gao; Urvi Aras (Clinical and Translational Science, 2023)
Abstract This analysis was conducted to inform dose selection of a combination of nivolumab plus ipilimumab for the treatment of sorafenib‐experienced patients with hepatocellular carcinoma (HCC). CheckMate 040 is an open‐label, multicohort, phase I/II trial in adults with advanced HCC that evaluated nivolumab monotherapy (0.1–10 mg/kg once every 2 weeks [q2w]) and the following three combinations of nivolumab plus ipilimumab: (1) nivolumab 1 mg/kg plus ipilimumab 3 mg/kg every 3 weeks (q3w) for four doses, followed by nivolumab monotherapy 240 mg q2w (arm A); (2) nivolumab 3 mg/kg plus ipilimumab 1 mg/kg q3w for four doses, followed by nivolumab monotherapy 240 mg q2w (arm B); and (3) nivolumab 3 mg/kg q2w plus ipilimumab 1 mg/kg every 6 weeks continuously (arm C). Exposure‐response relationships (efficacy and safety) were characterized using nivolumab and ipilimumab concentrations after the first dose (Cavg1) as the exposure measure. Objective tumor response (OTR) and overall survival (OS) improvements were associated with increased ipilimumab exposure (OTR: odds ratio 1.45, 95% confidence interval [CI], 1.13–1.86; OS: hazard ratio 0.86, 95% CI 0.75–0.98), but not nivolumab exposure (OTR: odds ratio 0.99, 95% CI 0.97–1.02; OS: hazard ratio 1.08, 95% CI 0.89–1.32). Hepatic treatment‐related and immune‐mediated adverse events were more common in arm A than in arms B or C. Nivolumab 1 mg/kg plus ipilimumab 3 mg/kg q3w for four doses, followed by nivolumab monotherapy 240 mg q2w had the most favorable benefit:risk profile in patients with advanced HCC.